Pengaruh Penggunaan Pupuk Hayati dan NPK Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium Cepa L.) - Bayu Adi; Musrif Musrif (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
The low productivity of shallots is caused by several constraints, namely cultivation techniques and high production costs. This study aims to determine the effect of the use of biological fertilizers, NPK and their interactions on the growth and production of shallot (Allium Cepa L.). This research was conducted from October 2019 to December 2019 in Tanganapada Village Jln. Sipanjonga, Betoambari District, Baubau City. The design used in this study was a factorial randomized block design (RAK) with two factors, namely Biological Fertilizer; H0: 0 mL/200 mL (biological; water), H1; 1 mL/200 mL (biological; water), H2; 2 mL/200 mL (biological; water), H3; 3 mL/200 mL (biological; water), H4; 4 mL/200 mL (biological; water) and NPK P0 fertilizer; 0 grams and P1; 1 gram which is grouped into 3 groups. The research response design included Plant Height, Number of Leaves, Number of Bulbs and Productivity. The results of this study showed that the H4P0 treatment had a significant effect on the parameters of the number of leaves and the use of NPK fertilizer with a level of 1 gram affecting the parameters of shallot plant height.